TEACHERS’ PERCEPTION ON CONTINUING PROFESSIONAL DEVELOPMENT AFTER COVID-19 PANDEMIC - Fajrinur Fajrinur; Ivvon Septina Bella; Cut Santika; Reza Novianda (Jurnal Scientia, 2022)
The researcher investigated two research questions on the teachers’ perception towards continuing professional development in Bireuen Regency at the time of covid-19. The first research question was the opinion on continuing professional development in general and the second one was going more in-depth to find out how this opinion differs after the time of Covid-19. 30 teachers from the six schools in Bireuen Regency were included in this research. All participants were asked to provide responses to questionnaires and interviews. This study used mixed methods as its research methodology in order to make the data obtained more comprehensive, valid, reliable and objective. As a result, among Continuing Professional Development (CPD) programs, ‘Network of Teachers Formed Specifically for the Professional Development’ had the greatest impact on teacher work before or after pandemic, with more than half of the respondents were found to be participating in the ‘Network of Teachers Formed Specifically for the Professional Development’ and they believe it has had a great impact on them.